An Experimental Study on Steel Fiber Effects in High-Strength Concrete Slabs - Elbialy, Samy; Elfarnsawy, Mahmoud; Salah, Mohamed; Abdel-Aziz, Ahmed; Ibrahim, Wael (Salehan Institute of Higher Education, 2025)
This study investigated the impact of varying steel fiber ratios by volume on the performance of HSC slabs. Incorporating steel fibers into high-strength concrete (HSC) has been shown to significantly enhance its mechanical properties, particularly by improving its load-bearing capacity. Furthermore, the addition of steel fiber reduces the reliance on traditional reinforcement bars, leading to a more efficient use of materials. This not only simplifies the construction process but also contributes to a reduction in overall construction costs. This study investigated the behavior of HSC slab specimens under loading and elevated temperatures. Three groups of specimens were created based on their thickness (8 cm, 12 cm, and 16 cm) using a single high-strength concrete mixture and four varying steel fiber proportions (0, 37.5, 75, and 150 kg/m³). Two-point monotonic loading was applied to each slab specimen until failure. To determine the splitting tensile strength, 12 cylinders were cast. Additionally, 84 cubes were cast to assess the effects of elevated temperatures and different cooling techniques on compressive strength (fcu). The results revealed that incorporating steel fibers into high-strength concrete slabs has a negligible effect on the concrete's density and compressive strength. However, it notably enhanced the splitting tensile strength and modulus of rupture. These improvements significantly boosted the material's resistance to cracking, making it more durable and better suited for applications requiring superior tensile performance. This is particularly important in structures subjected to dynamic or cyclic loading, where the risk of cracking and failure is greater. Doi: 10.28991/CEJ-2025-011-01-013 Full Text: PDF